(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The concept of«concept» is disclosed in the article, the concept of «soul», realized in the work of the poet of Yevgenia Mishankina, was analyzed, and it is also proved that the frequency of the use of the concept «soul» in poetry and in prose coincides. In total, 6 definitions of the given word are given in the article, which testifies to the diversity of semantic and conceptual modifications, about the possibilities of interpreting this concept depending on the intention of the individual, on his individual language picture of the world and language consciousness.